Pengaruh Pesan Keagamaan Dalam Nadham Maulid Al-Dhiyâ’ Al-Lâmi’ Terhadap Jamaah Majelis Taklim Al-Hidayat Gampong Peulanggahan Banda Aceh; Kajian Ritual Effect: The Influence of Religious Messages in Nadham Maulid Al-Dhiyâ’ Al-Lâmi’ on the Congregation of Al-Hidayat Majelis Taklim in Peulanggahan Village, Banda Aceh: A Ritual Effect Study - Syarifuddin; Rahmatillah , Cut Masthura; Abd Razak; Rahma Salbiah (An-Nahdah Al-'Arabiyah is published by Department of Arabic Language and Literature in cooperation with The Center for Research and Community Service (LP2M), 2024)
This study focuses on analyzing the religious messages in the ritual recitation of Nadham Maulid Al-Dhiyâ’ Al-Lâmi’, its impact on the congregation of Al-Hidayat Majelis Taklim and the community, as well as the motives and strategies for its preservation using the ritual effect approach. This research employs a qualitative method with a public opinion survey approach, gathering data through observation, interviews, and documentation studies. Data analysis is conducted through data reduction, presentation, and conclusion drawing, while data validity is ensured through continuous observation, increased rigor, and triangulation. The findings are as follows: First, the content includes messages of monotheism, praise for the Prophet, nobility, lineage, praises for the birth, and prophetic history; second, the religious impact on the lives of the congregation and the Acehnese community includes increased faith, love for the Prophet, adherence to Allah’s Sharia and the Prophet’s Sunnah, blessed life, improved morals, psychological therapy, and strengthened social relationships; third, the ritual art of reciting Nadham Maulid Al-Dhiyâ’ Al-Lâmi’ can be preserved due to the attraction to the familial network of the Prophet known as Ahlul Bait, as well as the traditional Hadrah music تركز هذه الدراسة على تحليل الرسائل الدينية في الطقوس القرائية لنظم مولد الضياء اللامع، وتأثيره على جماعة مجلس التعليم الهدى والمجتمع، وكذلك دوافع واستراتيجيات الحفاظ عليه باستخدام نهج تأثير الطقوس. تستخدم هذه الدراسة طريقة نوعية مع نهج مسح الرأي العام، ويتم جمع البيانات من خلال الملاحظة والمقابلات ودراسات التوثيق. يتم تحليل البيانات من خلال تقليل البيانات أو اختيارها، وعرضها واستخلاص النتائج، بينما يتم ضمان صحة البيانات من خلال الملاحظة المستمرة، وزيادة الدقة، والتثليث. النتائج التي تم الحصول عليها هي: أولاً، تتضمن المحتويات رسائل التوحيد، والصلاة على النبي، والشرف، والنسب، والثناء على المولد، والسيرة النبوية؛ ثانياً، التأثير الديني على حياة الجماعة والمجتمع الأتشي مثل زيادة الإيمان، والمحبة للنبي، والالتزام بشريعة الله وسنة النبي، وبركة الحياة، وتحسين الأخلاق، والعلاج النفسي، وتعزيز العلاقات الاجتماعية؛ ثالثاً، يمكن الحفاظ على فن الطقوس القرائية لنظم مولد الضياء اللامع، بسبب الجاذبية لشبكة الأسرة النبوية المعروفة بأهل البيت، وكذلك بسبب الموسيقى التقليدية للحدرة. Penelitian ini fokus pada analisis pesan keagamaan ritual pembacaan nadham maulid Al-Dhiyâ’ Al-Lâmi’, dampaknya terhadap jamaah majelis taklim al-Hidayat dan masyarakat, serta motif dan strategi pelestariannya dengan pendekatan ritual effect. Penelitian ini menggunakan metode kualitatif dengan pendekatan public opinion survey, yang pengumpulan datanya dilakukan melalui observasi, wawancara, dan studi dokumentasi. Analisis data dilakukan dengan reduksi atau pemilihan data, penyajian dan penarikan kesimpulan, sedangkan keabsahan data dilakukan melalui pengamatan berkesinambungan, peningkatan ketekunan, dan triangulasi. Hasil yang diperoleh adalah; pertama kandungan pesan tauhid, bershalawat, kemulian, nasab, puji-pujian atas kelahira, dan sirah naba; kedua, pengaruh keagamaan terhadap kehidupan jamaah dan masyarakat Aceh seperti peningkatan iman, kecintaan kepada Rasulullah, ketaatan kepada syariat Allah dan sunnah Rasulullah, keberkahahan hidup, peningkatan pada akhlak, terapi psikologi, dan penguatan hubungan sosial; ketiga seni ritual pembacaan nadham maulid Al-Dhiyâ’ Al-Lâmi’ dapat dipertahankan, selain disebabkan oleh adanya ketertarikan pada jaringan kekeluargaan Rasulullah yang diyakini dengan istilah ahlul bait juga disebabkan oleh lantunan musik tradisional hadrah.